A field study of lignite as a drying aid in the superheated steam drying of anaerobically digested sludge. (1st October 2015) - Hoadley, A.F.A.; Qi, Y.; Nguyen, T.; Hapgood, K.; Desai, D.; Pinches, D.
Abstract: Dried sludge is preferred when the sludge is either to be incinerated or used as a soil amendment. This paper focuses on superheated steam drying which has many benefits, because the system is totally enclosed, thereby minimising odours and particulate emissions. This work reports on field trials at a wastewater treatment plant where anaerobically digested sludge is dried immediately after being dewatered by belt press. The trials showed that unlike previous off-site tests, the sludge could be dried without the addition of a filter aid at a low production rate. However, the trials also confirmed that the addition of the lignite (brown coal) into the anaerobically digested sludge led to a more productive drying process, improved product quality and a greater fraction of the product being in the desired product size range. It is concluded that these results were achieved because the lignite helped to control the granule size in the dryer. Furthermore neither Salmonella spp or E coli were detected in the dried samples. Tests on spontaneous combustion show that this risk is increased in proportion to the amount of lignite used as a drying aid. Graphical abstract: Highlights: The results of onsite drying trials are reported using a rotary drum SHS dryer. Productivity was improved by using lignite (brown coal) as a drying aid. No biological activity was found for the dried products. Addition of lignite improves the final properties; heating value and humate profile. Addition of lignite makes the product more susceptible to spontaneous combustion.